2014
DOI: 10.1371/journal.pone.0102217
|View full text |Cite
|
Sign up to set email alerts
|

Increased Gut Permeability and Bacterial Translocation after Chronic Chlorpyrifos Exposure in Rats

Abstract: The epithelium's barrier function is crucial for maintaining homeostasis and preventing the passage of food antigens and luminal bacteria. This function is essentially subserved by tight junctions (TJs), multiprotein complexes located in the most apical part of the lateral membrane. Some gastrointestinal disease states are associated with elevated intestinal permeability to macromolecules. In a study on rats, we determined the influence of chronic, daily ingestion of chlorpyrifos (CPF, a pesticide that crosses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 36 publications
8
77
0
Order By: Relevance
“…In conclusion, our earlier morphological and molecular analyses showed that long-lasting exposure to CPF (an organophosphate insecticide observed as food residues) altered the maturation of the rat intestine and was associated with intestinal dysbiosis and BT towards sterile organs [4, 5]. In the present study, we confirmed the occurrence of BT and validated the use of molecular typing in rats exposed to CPF in utero and during lactation.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…In conclusion, our earlier morphological and molecular analyses showed that long-lasting exposure to CPF (an organophosphate insecticide observed as food residues) altered the maturation of the rat intestine and was associated with intestinal dysbiosis and BT towards sterile organs [4, 5]. In the present study, we confirmed the occurrence of BT and validated the use of molecular typing in rats exposed to CPF in utero and during lactation.…”
Section: Discussionsupporting
confidence: 84%
“…Several previous studies have investigated the effect of CPF on the intestinal wall (ileum and colon) [4, 5]. Exposure to CPF decreases the mRNA expression of genes encoding the tight junction proteins (including claudin-4 and zonula-1); this increases intestinal permeability, enables BT and activates the immune system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, another study indicated that CPF is biotransformed by cytochrome P450 in the upper part of the small intestine [9]. Lastly, Joly Condette et al’s rat study showed for the first time that exposure to a low dose of pesticide causes morphological changes in the intestinal epithelium, increases intestinal permeability and bacterial translocation, and is associated with an imbalance in the intestinal microbiota [10,11]. …”
Section: Introductionmentioning
confidence: 99%
“…Hispanics have a disproportionate disease burden for many common diseases related to vasculature (i.e., diabetes and cardiovascular disease) (82)(83)(84)(85)(86)(87)(88)(89)(90) that have also been shown to have microbiome-related disease variables in many other experimental contexts (91)(92)(93)(94)(95)(96)(97)(98)(99)(100)(101)(102)(103)(104). Dental health, bacterial infection, and peripheral vascular disease have many independent associations (105), and some of the etiology could be affected by systemic loosening of tight junctions as induced by organophosphates (78). In many other contexts, environmental pollutants have been shown to affect the microbiome (106), and here we show in humans the association between the composition of the microbiome and agricultural pesticide exposure.…”
Section: Discussionmentioning
confidence: 49%